Conductas disruptivas y su repercusión en el aprendizaje en estudiantes de Educación Básica de la Unidad Educativa Aurora Estrada y Ayala - Contreras Carrera, Stephanie Isabel (2024)
Disruptive behaviors of students in the classroom have been considered as a factor of multiple importance in the educational task, because these behaviors have a significant impact on the development of teaching and learning, understanding on the one hand that disruptive behaviors are those manifestations or inappropriate actions presented by students during the school day, which generate a dysfunctional climate in the classroom. On the other hand, learning is defined as a process in which the individual acquires knowledge based on his or her life experiences. The present descriptive study was established with the objective of analyzing the influence of disruptive behaviors in the learning process of Basic Education students of the Aurora Estrada y Ayala Educational Unit, in order to identify the type of disruptive behaviors that influence the learning process and based on the results recommend appropriate methodologies to the teachers of the educational center to eliminate or reduce such inappropriate behaviors and thus create a positive environment where effective teaching and learning can take place. In the first instance the work begins with its respective theoretical basis, which will allow describing the theoretical contributions from the point of view of different authors, in second instance, data collection is performed by applying the questionnaire of disruptive behaviors of Yenny Rocio Canccapa Silverio-Mery Yanet Canccapa (2015), on the other hand two observation sheets were also applied, one directed towards the students and the other directed towards the teachers. In conclusion, it was analyzed that disruptive behaviors influence the learning process of students because these behaviors interrupt class hours when the teacher is imparting knowledge.